2009
DOI: 10.1007/s11746-009-1383-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Components of North American Wild Rice (Zizania palustris)

Abstract: The content and composition of fatty acids, sterols, tocopherols, and c-oryzanol in wild rice (Zizania palustris) grown in North America were compared with those in regular brown rice (Oryza sativa L.). The lipid content of wild rice ranged from 0.7 to 1.1%, compared with 2.7% in regular brown rice. The lipids of wild rice comprised mainly linoleic (35-37%) and linolenic (20-31%) acids. Other fatty acids included palmitic (14.1-18.4%), stearic (1.1-1.3%), and oleic (12.8-16.2%). Wild rice lipids contained very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 18 publications
3
57
0
1
Order By: Relevance
“…Studies have shown that magnesium can improve insulin sensitivity by acting as a mild calcium antagonist and reduce the risk of type 2 diabetes [28,29]. In addition, WR lipids contain exceptional levels of hypothetically nutraceutical elements relative to that reported for regular brown rice, rice germ or wheat bran, including large amounts of phytosterols, phenolic acids, γ-oryzanols and tocotrienols [30]. WR had 10-times higher antioxidant activity than white rice, which signifies that WR prevention or attenuation of insulin sensitivity and undesirable metabolic effects is more effective than white rice and wheat starch [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that magnesium can improve insulin sensitivity by acting as a mild calcium antagonist and reduce the risk of type 2 diabetes [28,29]. In addition, WR lipids contain exceptional levels of hypothetically nutraceutical elements relative to that reported for regular brown rice, rice germ or wheat bran, including large amounts of phytosterols, phenolic acids, γ-oryzanols and tocotrienols [30]. WR had 10-times higher antioxidant activity than white rice, which signifies that WR prevention or attenuation of insulin sensitivity and undesirable metabolic effects is more effective than white rice and wheat starch [31].…”
Section: Discussionmentioning
confidence: 99%
“…RBOS and RBMC were analyzed for c-oryzanol by HPLC as previously reported [32]. A Finnigan Surveyor Plus HPLC system (Thermo Electron, Waltham, MA, USA) was used.…”
Section: Gamma-oryzanolmentioning
confidence: 99%
“…Many investigations on lipid fractions of rice brans have been published (Przybylski et al, 2009;Jennings and Akoh, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some reports have shown that the hydrolysis and oxidation of rice fat are responsible for rice aging and deterioration of grain flavor during storage, and low-oil rice cultivars are more suitable for storage (Zhou et al, 2002b). Therefore, it is important to determine the genetic basis of rice fat synthesis in order to further develop both high-oil and low-oil rice cultivars to address different market needs.Many investigations on lipid fractions of rice brans have been published (Przybylski et al, 2009;Jennings and Akoh, 2009). …”
mentioning
confidence: 99%